Transmission network expansion planning considering uncertainty in demand - Silva, Irenio de J.; Rider, Marcos J.; Romero, Ruben; Murari, Carlos A. F. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
This paper presents two mathematical models and one methodology to solve a transmission network expansion planning problem considering uncertainty in demand. The first model analyzed the uncertainty in the system as a whole; then, this model considers the uncertainty in the total demand of the power system. The second one analyzed the uncertainty in each load bus individually. The methodology used to solve the problem, finds the optimal transmission network expansion plan that allows the power system to operate adequately in an environment with uncertainty. The models presented are solved using a specialized genetic algorithm. The results obtained for several known systems from literature show that cheaper plans can be found satisfying the uncertainty in demand.
Keywords: direct current (dc) model; genetic algorithm; long-term transmission network expansion planning; uncertainty in demand